Effectiveness of a comprehensive lifestyle modification program for asthma patients: a randomized controlled pilot trial - Pokladnikova, Jitka; Selke-Krulichova, Iva (The Journal of asthma, 2013)
OBJECTIVE: The aim of the study was to investigate the effectiveness and feasibility of conducting a complementary 8-week comprehensive lifestyle modification program (CLMP) compared to standard care in patients with bronchial asthma over a 6-month period. METHODS: This was a randomized controlled pilot trial with two groups: intervention (N = 15) group and attention-placebo control (N = 14) group. The intervention group received an 8-week CLMP in addition to standard care. Quality of life, asthma control, lung function, reduction of rescue medication, perceived stress, and psychosocial and spiritual status were measured at the end of the intervention and at the 4-month follow-up. RESULTS: In the intervention group, there was a statistically significant difference in the improvements of quality of life, asthma control, lung function, and the reduction of rescue medication intake at both the end of the intervention and at the 4-month follow-up, with no change being observed in the control group. Significant stress reduction and greater psychosocial and spiritual well-being were observed during the 8-week CLMP in the intervention group. At the end of the intervention, the measures of stress and psychological and spiritual well-being reached statistical significance. CONCLUSIONS: Preliminary findings suggest that adding a CLMP to standard care in patients with bronchial asthma offers greater clinical benefit than standard care alone and also suggest that conducting a large randomized clinical trial is feasible.
Keywords: Anti-Asthmatic Agents; Behavior Therapy; Female; Quality of Life; behaviorální terapie; ženské pohlaví; Life Style; životní styl; kvalita života; lidé; antiastmatika; Pilot Projects; pilotní projekty; Asthma; neparametrická statistika; Male; bronchiální astma; lidé středního věku; Respiratory Function Tests; Statistics, Nonparametric; mužské pohlaví; respirační funkční testy; Middle Aged; Humans